Hubungan Karakteristik Komunikasi Petani dengan Tingkat Kedinamisan Kelompok Petani - Andi Suci Anita; Edward Zubir (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2017)
The success of agricultural development is closely connected with the extent of innovation information received by farmers either individuals or groups. Farmer groups be an entry point in the diffusion of innovation by farmers. Approaches to see how far the effectiveness of the group is through a group dynamics approach. The research method used explanatory research, research that explains the relationship between variables through hypothesis testing. The research proves that all communication characteristics significantly associated with the level of the dynamics of the group. The higher the social participation, the more intense the communication, the higher the height of media access and participation in education, the more dynamic is also a group. Elements of group dynamics that purpose, structure and function, atmosphere, coaching and effectiveness significantly associated with all the communication variables. Pressure group only related to social participation and intensity of communication. Only cohesiveness of the group that did not have anything to do with the characteristics of the group